Age effect on autobiographical memory specificity: A study on autobiographical memory specificity in elderly survivors of childhood trauma. (March 2017) - Wittekind, Charlotte E.; Jelinek, Lena; Kleim, Birgit; Muhtz, Christoph; Moritz, Steffen; Berna, Fabrice
Abstract: Background and objectives: Post-traumatic stress disorder (PTSD) is accompanied by altered autobiographical memories (AM) of the traumatic incident itself as well as of non-trauma-related events. Several studies have shown that trauma-exposed individuals developing PTSD have a reduced capacity to access specific past events that are not related to the traumatic event compared to those who do not develop PTSD. However, one study including a group of elderly adults did not find significant differences in AM between PTSD and non-PTSD participants. The present study investigated whether PTSD is associated with impaired AM of trauma-related and non-trauma-related memories in the elderly. Method: Forty-four elderly participants, displaced during childhood from former German territories after the end of World War II (WWII), were examined. This group comprised 19 participants with and 25 participants without PTSD. These participants were compared to 23 non-traumatized non-displaced elderly participants. Results: PTSD, non-PTSD and non-traumatized participants do not differ significantly in their ability to recall specific memories of their past. Moreover, participants with PTSD did not recall more trauma-related memories than non-PTSD participants. Limitations: The traumatized participants reached for assessment might represent the most resilient individuals, which might constrain generalizability of our results to other trauma populations. Conclusions: This study confirms preliminary evidence that PTSD is not associated with AM impairment in the elderly. We suggest that aging may alter the relationship between trauma and AM impairment in traumatized participants with PTSD, which need to be confirmed by longitudinal studies. Highlights: Post-traumatic stress disorder (PTSD) usually alter autobiographical memory (AM). Traumatized elderly with and without PTSD were compared to non-traumatized elderly. Memory specificity did not differ across the three groups. Aging may alter the relationship between trauma and AM impairment in PTSD.